Les Banove hiše v Artičah kot zgodovinski arhiv - Čufar, Katarina (Acta silvae et ligni, 2013)
We conducted a survey of wood and performed dendrochronological dating of beams from the external walls of the old Ban's House in the village of Artiče near Brežice. The logs were made of different wood species, with different oaks among them, i.e. sessile oak (Quercus petraea), pedunculate oak (Quercus robur) and Turkey oak (Quercus cerris), as well as sweet chestnut (Castanea sativa) and Norway spruce (Picea abies). Based on dendrochronological dating of the outermost tree-rings, the beams were divided into groups having the end dates of 1535 (2 beams - Turkey oak and pedunculate / sessile oak), 1563-1592 (8 logs - 5 Turkey oak and 3 pedunculate / sessile oak), 1613-1720 (3 logs - pedunculate / sessile oak), 1779-1792 (7 logs - 4 pedunculate / sessile oak and 3 chestnuts) and Ž 1913 (10 spruce logs). The beams of different wood species and with different end dates were mixed across the walls, indicating that the house had been rebuilt several times and that the timber from the same house or other buildings was re-used. Our assessments concerning different end dates and selection of several wood species were supplemented with information from forestry sources. They showed that the wood was very likely of local origin.
Keywords: identifikacija lesa; dendrokronologija; datiranje; stavbna dediščina; stavbni les; Slovenia; Slovenija